2016
DOI: 10.1111/liv.13312
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of miRNAs in serum in severe acute drug induced liver injury and their prognostic significance

Abstract: Background and Aims Drug induced liver injury (DILI) is challenging because of the lack of biomarkers to predict mortality. Our aim was to describe miRNA changes in sera of subjects with acute idiosyncratic DILI and determine if levels of miRNAs were associated with 6 month mortality. Methods Clinical data and sera were collected from subjects enrolled in the Drug Induced Liver Injury Network prospective study. miRNAs were isolated from serum obtained from 78 subjects within 2 weeks of acute DILI and followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 35 publications
0
43
0
2
Order By: Relevance
“…The prognostic performance of GLDH and miR‐122 was not determined in the current study because these biomarkers were not measured in the DILIN patient cohort (due to sample volume limitations) where outcome data was systematically collected. However, semiquantitative measurements of miR‐122 have previously been conducted in a subset of DILIN patients . In contrast to the data observed in APAP‐induced hepatotoxicity, reduced serum levels of miR‐122 and albumin were observed in patients that died within 6 months of DILI onset compared with patients who recovered.…”
Section: Discussionmentioning
confidence: 87%
“…The prognostic performance of GLDH and miR‐122 was not determined in the current study because these biomarkers were not measured in the DILIN patient cohort (due to sample volume limitations) where outcome data was systematically collected. However, semiquantitative measurements of miR‐122 have previously been conducted in a subset of DILIN patients . In contrast to the data observed in APAP‐induced hepatotoxicity, reduced serum levels of miR‐122 and albumin were observed in patients that died within 6 months of DILI onset compared with patients who recovered.…”
Section: Discussionmentioning
confidence: 87%
“…In one study conducted by the DILIN, miRNAs were quantified in serum collected from patients with idiosyncratic DILI within 2 weeks of the onset of injury. 58 While miR-122 levels in these patients were elevated compared with healthy controls, patients who experienced liver failure within 6 months of onset had significantly reduced levels of this miRNA (and albumin) compared with the patients who recovered. However, a recent study showed that miR-122 had the best performance for predicting patients after an acetaminophen overdose who would develop serum ALT >1000 U/L.…”
Section: Prognostic Biomarkersmentioning
confidence: 81%
“…This observation has been recapitulated in human studies. Various miRNA profiling studies in humans with acetaminophen‐induced or idiosyncratic DILI have confirmed that miR‐122 is a robust biomarker of hepatotoxicity . Significant elevations in this biomarker are often observed prior to ALT elevations in patients who have consumed toxic doses of acetaminophen …”
Section: Promising New Dili Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations